Improving students’ higher order thinking skills in learning health systems using mobile-based instructional approach - S., Suharno; S., Irmawan; H., Saputro; N., Agung Pambudi; J., Jumintono (TMU, 2022)
Aims Learning health systems are healthcare systems in which awareness formation processes are inserted into daily practice to provide constant development in care. Many students have difficulty completing the health systems courses due to a lack of Higher-Order Thinking Skills (HOTS). Therefore, this study aims to improve students’ HOTS using a mobile-based instructional approach. Materials & Methods The enhanced HOTS is measured using indicators of critical and creative thinking processes known as Bloom’s taxonomy concept. Furthermore, this is experimental research with a pre-test-post-test random control group pattern and ADDIE technique to develop the mobile-based instructional Approach. The study involved 120 students who were evenly divided into the experimental class and the control class. Respondents were selected from 650 SMK students in Central Java using the random cluster sampling method. Findings Based on the results, this is evidenced by the ability to answer challenging questions associated with critical and creative reasons. Conclusion Therefore, using a mobile-based instructional Approach supports independent learning.